2001
DOI: 10.1093/brain/124.7.1373
|View full text |Cite
|
Sign up to set email alerts
|

Left minineglect in dyslexic adults

Abstract: We searched for a core mechanism underlying the diverse behavioural and sensorimotor deficits in dyslexic subjects. In psychophysical temporal order judgement and line motion illusion tasks, adult dyslexics processed stimuli in the left visual hemifield significantly (approximately 15 ms) more slowly than normal readers, indicating a left-sided 'minineglect'. Furthermore, abrupt stimuli captured attention in both visual hemifields less effectively in dyslexics than in normal readers. These abnormalities could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
5
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(114 citation statements)
references
References 48 publications
8
100
5
1
Order By: Relevance
“…In a previous study in our laboratory, we found that developmentally dyslexic children were somewhat impaired in temporal acuity tasks in all sensory modalities investigated, relative to their agematched controls (Laasonen et al, 2000). Other Finnish studies (Hari & Kiesilä, 1996;Hari et al, 2001;Hari, Valta, & Uutela, 1999;Helenius, Uutela, & Hari, 1999;Kujala et al, 2000) have found impaired processing of rapid auditory and visual sequences in adult dyslexics, but these studies did not include multiple modality comparisons.…”
mentioning
confidence: 60%
“…In a previous study in our laboratory, we found that developmentally dyslexic children were somewhat impaired in temporal acuity tasks in all sensory modalities investigated, relative to their agematched controls (Laasonen et al, 2000). Other Finnish studies (Hari & Kiesilä, 1996;Hari et al, 2001;Hari, Valta, & Uutela, 1999;Helenius, Uutela, & Hari, 1999;Kujala et al, 2000) have found impaired processing of rapid auditory and visual sequences in adult dyslexics, but these studies did not include multiple modality comparisons.…”
mentioning
confidence: 60%
“…The form effects Sireteanu et al, 2005). Adults without visuospatial deficits tend to overestimate the left visual field because of the advantage of right hemispheric processing; however, individuals with hemineglect usually ignore their left extrapersonal space (Halligan & Marshall, 1992), and those with dyslexia process stimuli in the left visual field more slowly (Hari, Renvall, & Tanskanen, 2001). In previous studies (Hari et al, 2001;Roeltgen & Roeltgen, 1990;Sireteanu et al, 2005), it has been suggested that people with developmental dyslexia showed a left "minineglect"-an immature attention pattern due to the right parietal lobe hypofunction caused by a magnocellular deficit.…”
Section: Resultsmentioning
confidence: 99%
“…The most prominent findings here were aberrant connectivity between anterior caudate and a TPJ subregion functionally connected to DAN regions such as the intraparietal sulcus, putative human frontal eye fields, and dorsolateral prefrontal cortex. Many studies have highlighted abnormalities in visuospatial attention in RD (Facoetti and Molteni 2001;Hari et al 2001;Facoetti et al 2003Facoetti et al , 2006Sireteanu et al 2005;Liddle et al 2009;Facoetti, Corradi et al 2010;Facoetti, Trussardi et al 2010). Converging evidence also suggests that difficulties in visuospatial attention are an important predictor of reading abilities (Valdois et al 2004;Shaywitz and Shaywitz 2008;Franceschini et al 2012Franceschini et al , 2013.…”
Section: Discussionmentioning
confidence: 99%